Study on Effect of Vehicle Side Mirror Base Position on Noise - Ahmad Kamal Iqmal Azman,; Rahmah Mahmudin, (Progress in Engineering Application and Technology, 2024)
The position of side mirrors plays a crucial role in ensuring optimal visibility and safety during vehicle operation. Additionally, the design and placement of side mirrors can have a significant impact on the generation and propagation of aerodynamic and wind-induced noise. This study presents an investigation into the relationship between side mirror base positioning and noise generation using ANSYS, a powerful engineering simulation software. The study focuses on utilizing computational fluid dynamics (CFD) simulations within the ANSYS platform to analyze the aerodynamic performance of angular and horizontal side mirror positions. By considering different mirror angles, the research aims to identify the optimal side mirror base position that minimizes noise generation while maintaining adequate visibility. To prepare for this research, a model was scanned using a 3D scanner, and the base will be modified using the SolidWorks software, and the simulation ran using the ANSYS software. To execute a test with specific conditions for the new model, the boundary condition will be specified towards it in the ANSYS software.  Three streamline velocity values (80 km/h, 100 km/h, 120 km/h) were chosen as references. The results of the analysis included the side mirror's acoustic contour and sound pressure level. The horizontal base produces a maximum acoustic power level of 103.41 dB when travelling at a high speed of 120 km/h. The maximum acoustic power level for angular base, which travels at 120 km/h is 101.48 dB. In summary, horizontal base side mirror has a higher acoustic power level than angular base side mirror.